Social determinants and psychological distress among Aboriginal and Torres Strait islander adults in the Australian state of Victoria: A cross-sectional population based study. (March 2015) - Markwick, Alison; Ansari, Zahid; Sullivan, Mary; McNeil, John
Abstract: Aboriginal and Torres Strait Islander adults in the Australian state of Victoria have a higher prevalence of psychological distress than their non-Aboriginal and Torres Strait Islander counterparts. We sought to explain this inequality, focussing on the social determinants of health. We used population-based survey data from the 2008 Victorian Population Health Survey; a cross-sectional landline computer-assisted telephone survey of 34, 168 randomly selected adults. We defined psychological distress as a score of 22 or more on the Kessler 10 Psychological Distress scale. We used logistic regression to identify socio-demographic characteristics and social capital indicators that were associated with psychological distress. We then created multivariable models to explore the association between psychological distress and Aboriginal and Torres Strait Islander status that incorporated all significant socioeconomic status (SES) and social capital variables, adjusting for all non-SES socio-demographic characteristics. Aboriginal and Torres Strait Islander Victorians (24.5%) were more than twice as likely than their non-Aboriginal and Torres Strait Islander counterparts (11.3%) to have psychological distress (odds ratio (OR) = 2.56, 95% confidence interval; 1.67–3.93). Controlling for SES, negative perceptions of the residential neighbourhood, lack of social support from family, social and civic distrust, and all non-SES socio-demographic variables (age, sex, marital status, household composition, and rurality), rendered the previously statistically significant inequality in the prevalence of psychological distress, between Aboriginal and Torres Strait Islander Victorians and their non-Aboriginal and Torres Strait Islander counterparts, insignificant at the p = 0.05 level (OR = 1.50; 0.97–2.32). Psychological distress is an important health risk factor for Aboriginal and Torres Strait Islander adults that has yet to be widely acknowledged and addressed. Addressing the underlying inequalities in SES and social capital may be the key to addressing the inequality in psychological distress. Highlights: Aboriginal Victorians have a higher prevalence of psychological distress. Inequalities in SES and social capital largely explain the inequality in psychological distress. Aboriginal compared with non-Aboriginal Victorians have lower bonding social capital. Psychological distress is a key health risk factor among Aboriginal Victorians.